Breastfeeding today means thinking about the future: the place of women in contemporary breastfeeding-promotion discourses (Brazilian Journal of Health Research, 2019)
Introduction: The Brazilian Ministry of Health has intensified the production of educational materials on breastfeeding for professionals and the general population in the last two decades. Objective: Assessing the recent materials developed to promote and guide breastfeeding; identifying similarities and differences between discourses targeting pregnant and lactating women, as well as health professionals directly related to propositions for women. Methods: The enunciation theory by Émille Benveniste was the adopted theoretical-methodological basis. According to this theory, the speaker is not the one who constitutes itself as the speaker, but as the one who “implants the other before itself”. Results: Although the oneself or subject of a discourse enunciation (Ministry of Health) remains in place, there are significant distinctions in the approach towards women. Manuals available for health professionals commonly represent women as individuals endowed with the subjectivity and protagonism of breastfeeding. Overall, materials targeting women are objective, they present normative language and become instruments of child health policies. Conclusion: Official discourses act as “absolute discourse”, as mentioned by Eliseo Verón. In other words, they act as the one that brings the illusion of truth by hiding the production of social conditions. Therefore, there is the need of understanding how the spoken object is constituted in these discourses and of revealing how these discourses construct subject positions and power relationships among State, mothers and society.